Agama dan Sains dalam Struktur Pembidangan Studi Islam di Indonesia - Muhammad Fiqih Syamsul Arifin; Erfan Efendi; Nina Sutrisno Yanti Nurhayati (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2022)
Modernity has provided a distinction between religion and science as advised by Western secularization. However, the Indonesian administration does not practice such a treatment, even the structure of the field of Islamic studies in educational schools indicates a link between religion and science. This article aims to comprehend 1) the interrelation of religion and science in the Islamic studies field structure, 2) the forming background of the paradigm of the Islamic studies structure as a critical study, and 3) its implications for the Islamic studies development in Indonesia. To bridge the discussion of this problem, the relevant descriptive research method is used to collect library data. The study found that 1) the Islamic studies field structure is integrative, 2) the forming backgroun of the typology formation cannot escape the influence of Western education culture on Muslim scientists as well as the Indonesian values that regards religious and state values in a symbiotic way, and 3) the impact of Islamic scholarship integration toward paradigm on systems and learning methods in Indonesia. Modernitas telah memisahkan antara agama dan sains sebagaimana dalam sekularisasi Barat. Namun, perlakuan seperti itu tidak dilakukan oleh pemerintah Indonesia, bahkan struktur bidang studi Islam di lembaga-lembaga pendidikan menunjukkan adanya keterkaitan antara agama dan sains. Artikel ini bertujuan untuk memahami 1) keterkaitan agama dan sains dalam struktur bidang studi Islam, 2) latar belakang pembentukan paradigma struktur studi Islam sebagai studi kritis, dan 3) implikasinya bagi perkembangan studi Islam di Indonesia. Untuk menjembatani pembahasan masalah ini, metode penelitian deskriptif yang relevan digunakan untuk mengumpulkan data kepustakaan. Dalam kajian ini, ditemukan bahwa 1) struktur bidang kajian Islam bersifat integratif, 2) latar belakang pembentuk pembentukan tipologi tidak lepas dari pengaruh budaya pendidikan Barat terhadap ilmuwan Muslim serta nilai-nilai Indonesia yang memandang nilai agama dan negara secara simbiosis, dan 3) dampak integrasi keilmuan Islam terhadap paradigma sistem dan metode pembelajaran di Indonesia.